A Quantum-Resistant Advanced Metering Infrastructure - Lagrota, Vinícius; Filomeno, Mateus de L.; Dib, Leonardo de M. B. A.; López, Julio; Ribeiro, Moisés V. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2025)
This paper focuses on quantum-resistant cryptographic schemes to enhance the security of smart metering against threats from both quantum and classical computers. In this sense, we consider FrodoKEM and CRYSTALS-Kyber quantum-resistant as asymmetric cryptographic schemes and AES-GCM as a symmetric one. Moreover, we detail the design and implementation of a dedicated cryptographic module customized to ensure quantum-resistant advanced metering infrastructure (QR-AMI). Analysis based on experimental implementation shows the viability of a QR-AMI anchored on dedicated cryptographic modules implemented on a microcontroller (low-power processor) or a system-on-a-chip device.